Lipoxygenase pathways in Homo neanderthalensis: functional comparison with Homo sapiens isoforms - Pavlos Chaitidis; Susan Adel; Monika Anton; Dagmar Heydeck; Hartmut Kuhn; Thomas Horn (Journal of Lipid Research, 2013)
Lipoxygenases (LOX) have been implicated in biosynthesis of pro- and anti-inflammatory mediators, and a previous report suggested compromised leukotriene signaling in H. neanderthalensis. To search for corresponding differences in leukotriene biosynthesis, we screened the Neandertal genome for LOX genes and found that, as modern humans, this archaic hominid contains six LOX genes (nALOX15, nALOX12, nALOX5, nALOX15B, nALOX12B, and nALOXE3) and one pseudogene. In the Neandertal genome, 60–75% of the amino acids of the different human LOX isoforms have been identified, and the degree of identity varies between 96 and 99%. Most functional amino acids (iron ligands, specificity determinants, calcium and ATP-binding sites, membrane-binding determinants, and phosphorylation sites) are well conserved in the Neandertal LOX isoforms, and expression of selected neandertalized human LOX mutants revealed no major functional defects. However, in nALOX12 and nALOXE3, two premature stop codons were found, leading to inactive enzyme species. These data suggest that ALOX15, ALOX5, ALOX15B, and ALOX12B should have been present as functional enzymes in H. neanderthalensis and that in contrast to lower nonhuman primates (M. mulatta) and other mammals (mice, rats), this ancient hominid expressed a 15-lipoxygenating ALOX15. Expression of ALOXE3 and ALOX12 was compromised, which might have caused problems in epidermal differentiation.